Brassica glucosinolate rhythmicity in response to light-dark entrainment cycles is cultivar-dependent. (October 2018) - Soengas, Pilar; Cartea, M. Elena; Velasco, Pablo; Francisco, Marta
Highlights: Brassica cultivars keep track the time of the day to coordinate their defenses. The period and amplitude of GSLs circadian outputs were cultivar-dependent. A robust rhythmic behavior was found for the aliphatic GSLs: SIN and GNA. The plant clock can be re-entrained for GSLs accumulation after free-running conditions. Abstract: Coordination of plant circadian rhythms with the external environment provides growth and reproductive advantages to plants as well as enhanced resistance to insects and pathogens. Since glucosinolates (GLSs) play a major role as plant defensive compounds and could affect the palatability and health value of edible crops, the aim of this study was to investigate the species-specific patterns in circadian rhythmicity of these plant phytochemicals. Five different GLS-containing cultivars, from three Brassica crop species were studied. Plants were entrained to light-dark cycles (LD) for five weeks prior to release them into continuous light (LL). GLSs levels were monitored during five consecutive days (two days at LD conditions and three days at LL). The remaining plants were re-entrained to LD cycles (Re-LD plants) and GLS levels were studied as stated before during two consecutive days. Results showed that the period and amplitude of GLSs circadian outputs were cultivar-dependent. In addition, we assessed that the plant endogenous clock can be re-entrained for GLSs accumulation after a period of free-running conditions. Together, these data suggests that Brassica cultivars keep track the time of the day to coordinate their defenses. The demonstration of the cultivar-specific circadian effect on the GLSs levels in plants of different Brassica cultivars have the potential to identify new targets for improving cultivar phytochemicals using temporally informed approaches. In addition, provides an exceptional model to study the complexity of signal integration in plants.